Structural Changes in Temperature and Precipitation in MENA Countries - (:unkn) unknown (My University, 2023)
This paper evaluates the extent of climate variability in the Middle East and North Africa (MENA) region using time series structural change tests. The MENA region is highly susceptible to climate change, being one of the driest and most water-scarce regions in the world. The study aims to identify structural breaks in temperature and precipitation time series from 1901 to 2012. Specifically, a statistical analysis is performed based on a structural change model (Bai and Perron 1998, 2003a) for temperature and precipitation across 19 countries. The results indicate significant structural changes in temperature and precipitation patterns during the observation period, and suggest that climate variability has indeed begun to occur in all study area, with 1990 marking a turning point in terms of global warming. North African countries, Qatar, and the United Arab Emirates experienced a large number of breaks in temperature variables between 1901 and 2012, while other countries experienced fewer breaks. With regards to the seasonal aspect of precipitation, the individual rainfall Seasonality Index results demonstrate strong seasonal variability of rainfall from one year to another. Results show that rainfall in MENA countries is irregular throughout the year and that it ranges from seasonal to extremely seasonal throughout the study period. These findings have important implications for water resources management, agriculture, human health, and ecosystems in the region.
Keywords: African Research